(untitled) (Research, Society and Development, 2022)
Game-based learning (GBL) refers to an innovative approach arising from the use of games that have educational value for teaching purposes. Although several studies have been carried out relating games and teaching, few studies have explored the effectiveness of using game-based learning in the education of medical courses. This work aims to carry out a literature review to assess the effectiveness of this new methodology in teaching in the field of medicine. The research was carried out in the following databases: PubMed, Biblioteca Virtual em Saúde (BVS) and Cochrane. The terms contained in the DeCs were used: "Experimental Games", "Teaching", "Education of Graduation in Medicine" in Portuguese and English, also considering their synonyms, in combinations and associations with Boolean operators. Among the 529 articles retrieved, 38 were selected to be read in full. The results show that GBL strategies are as efficient as traditional classes, presenting the difference against the latter because they are more conducive to student engagement, as well as fun and interactive. The use of Game-Based Learning techniques promotes the teaching and learning of topics associated with Medical Sciences in Higher Education, and can be as efficient or more efficient than the teaching models traditionally adopted. Also, GBL promotes the necessary motivation for adult students in their learning process, being this is an important differential compared to other methodologies based on the simple exposition of contents by the teacher.